Storage Stability Enhancement of Lactic Acid Beverage Using Anti-MDA Lactiplantibacillus plantarum NJAU-01: The Antioxidant’s Role - Yuehao Wu; Menghao Zhao; Suyun Li; Siyu Liu; Song Gao; Rui Liu; Mangang Wu; Hai Yu; Qingfeng Ge (Foods)
This study evaluated the inhibitory efficacy of Lactiplantibacillus plantarum NJAU-01 (NJAU-01) on oxidation associated with malondialdehyde (MDA) and utilized the bacteria in a functional lactic acid beverage. The antioxidant capacity of the bacteria was measured in vitro, the production conditions (inoculum, fermentation time, and sugar addition) of the lactic acid beverage were optimized, and the effects of NJAU-01 on antioxidant, flavor profile, and storage stability of lactic acid beverages were investigated. The results revealed that NJAU-01 exhibited a high tolerance towards MDA at 40 mM, and that it also exhibited outstanding antioxidant capacity in vitro and antioxidant enzyme activity throughout its growth stage. The beverage demonstrated an elevated antioxidant capacity and efficiently eliminated MDA. Additionally, the NJAU-01 lactic acid beverage could be stored at 4 °C for 21 days, exhibiting stable sensory attributes and strong resistance against lipid peroxidation. The study yielded insights into the role of NJAU-01 in improving the storage stability of lactic acid beverages thereby contributing to a deeper understanding of the specific mechanisms by which probiotics enhance beverage quality. These findings can facilitate a more effective utilization of this knowledge in the food industry.